[Retracted] Effect of a dual tire pressure on the design parameters of thick asphalt pavements using finite element freeware (2016)
The effect of a dual tire pressure on the design parameters of thick asphalt pavements using finite element freeware EverStressFE©1.0 is evaluated. This is trying to represent more adjusted the footprint shape and intensity of stress generated by the tires of vehicles. To validate the elastic multilayer EverStress©5.0 software was used. The results of the deformations can be concluded that the asphalt pavement designs made with analytical methods may be slightly oversized and consequently increase the cost of construction of pavements. This study marks a route to analyze the sensitivity of various factors that may affect the design of asphalt pavements. Future research is expected to integrate dynamic conditions by introducing results of field tests to full scale.